Total Economic Value in Investment Analysis - Sudarsono Soedomo (Institut Pertanian Bogor (IPB University), 2013)
Forest ecosystems are often defeated in decisions about investment and economic development. There is a very wide gap between policy makers and development investment on the one hand and environmentalists on the other hand, who see the forest ecosystem from the perspective of ecology and environment. The first party considers that forest ecosystems have a low value, while the second party often shows very fantastic figures about the economic value of forests. From the second party's point of view, the first party could be ignorant or having a short-term interest; while from the first party's point of view, the second party loves to produce the figures that are too good to be true. As a result, the total economic value of ecosystems is not only ignored as a consideration in investment decisions, but the total economic value of ecosystems has been seen as a boring scientific joke. Why did the gap occur and how to close the gap will be discussed in this paper. Economic valuation of ecosystem needs to be done more realistically so that the results are more plausible before policy makers. On the contrary, policy makers need to be aware that once a species vanished it never goes back.Keywords: ecosystem, goods and services, value, trade-off, double counting DOI: 10.7226/jtfm.19.3.201